Effect of different ceramic primers on shear bond strength of resin-modified glass ionomer cement to zirconia. Issue 22 (16th November 2016) - Alnassar, Talal; Ozer, Fusun; Chiche, Gerard; Blatz, Markus B.
Abstract: Purpose: This study evaluated and compared the effect of different ceramic primers on the shear bond strength of RMGIC to zirconia with and without air-particle abrasion.Material and Methods: 120 zirconia square specimens (5 mm × 5 mm × 2 mm) were fabricated. Half of the specimens were air-particle abraded (A) and the other half were left untreated (NA). Both groups were further divided into six subgroups ( n = 10). Composite cylinders (2.9 mm × 3.0 mm) were fabricated and bonded to the zirconia samples with RMGIC (RelyX Plus) after different priming methods: no ceramic primer (group NS); Z-Prime (group ZP); Clearfil ceramic primer (group CP); cleaned with Ivoclean then Monobond plus (IV/MS); Monobond plus (group MS); and Rely X ceramic primer (group RX). Specimens were rinsed, stored in distilled water, and thermocycled (TC) for 10, 000 cycles between 5 and 60 °C with a dwell time of 15s. Data were analyzed with two-way ANOVA and the Tukey–Kramer method test ( a = .05).Results: air-particle abrasion significantly affected bond strength of RMGIC to zirconia regardless of the primer used ( p < 0.001 for all primers and the control). After TC, A-ZP (11.1 ± 0.6 MPa), A-CP (11.9 ± 0.6 MPa), and A-MS (11.9 ± 0.5 MPa) revealed the highest shear bond strength values, while NA-NS (2.9 ± 0.3 MPa) and NA-RX (4.7 ± 0.5 MPa) had the lowest. Failure modes were primarily adhesive.Conclusion: air-particle abrasion with aluminum oxide and application of MDP-based ceramic primers provide the highest bond strength of RMGIC to zirconia.